Modafinil. Armodafinil. The use of eugeroics in assisting the treatment of depression, bipolar disorder, and schizophrenia. Benefits, drawbacks, and adverse effects - Kandefer, Norbert; Jaremek, Anna; Kępa, Joanna; Wyszkowski, Michał; Grabarczyk, Aleksandra; Pawlak, Anna; Grad, Sylwia; Gregorek, Paweł; Gregorek, Małgorzata; Loryś, Laura; et al. (Journal of Education, Health and Sport, 2023)
Modafinil is used to treat narcolepsy with cataplexy and is also being extensively studied to find new therapeutic uses. In recent years, there have been reports suggesting the potential benefits of modafinil in the treatment of psychiatric illnesses such as depression and bipolar depression. In the case of depression, modafinil can be used as an adjuvant or as monotherapy in patients who do not respond sufficiently to antidepressants. Studies have shown that modafinil improves symptoms of depression, reduces fatigue and improves cognitive function. There are also reports of a beneficial effect of modafinil in the treatment of seasonal depression. For bipolar depression, modafinil can be used as an adjunct therapy during the depressive phase, particularly in patients experiencing slowness, lethargy and loss of pleasure. Studies suggest that modafinil may improve depressive symptoms without inducing manic episodes. There are also data indicating modafinil’s potential efficacy in treating negative symptoms and improving cognitive function in patients with schizophrenia. In conclusion, modafinil appears to be a promising drug in aiding the treatment of various psychiatric illnesses.